Thirty-day Complications and Readmission Rates in Elderly Patients After Shoulder Arthroplasty. (November 2018) - Koh, Justin; Galvin, Joseph W.; Sing, David C.; Curry, Emily J.; Li, Xinning
Abstract : Introduction: Shoulder arthroplasty procedures are increasingly being performed in older patients despite an increased perioperative risk. The purpose of this study is to determine the complications and 30-day readmission rates in the elderly population after shoulder arthroplasty and hemiarthroplasty. Methods: Total shoulder arthroplasty, reverse total shoulder arthroplasty, and hemiarthroplasty cases were collected from the National Surgical Quality Improvement Program database from 2006 to 2015. The 30-day complication and readmission rates, surgical time, discharge destination, and total hospital length of stay were calculated, comparing patients by age (elderly: ≥80 years; older: 65 to 79 years; younger: <65 years). Multivariable logistic regression analysis was performed to identify variables associated with any complication within 30 days of surgery. Results: Of 11, 450 patients, 1, 956 (17.1%) underwent shoulder hemiarthroplasty and 9, 494 (82.9%) underwent total shoulder arthroplasty. By age group, 1, 708 (14.9%) were ≥80, 6, 073 (53.0%) were 65 to 79, and 3, 669 (32.0%) were <65. The overall 30-day postoperative complication rate was significantly higher in elderly patients (15.3% versus 8.2% versus 6.8%; P < 0.001), length of stay (2.6 versus 2.1 versus 1.8 days; P < 0.001), and unplanned readmissions (5.5% versus 2.6% versus 2.3%; P < 0.001). The strongest independent variables significantly associated with any complication included revision arthroplasty indication (odds ratio [OR], 4.34; P < 0.001), fracture indication (OR, 4.14; P < 0.001), and history of cardiac disease (OR, 2.33; P < 0.001), followed by elderly age (OR, 2.01; P < 0.001). Conclusions: The 15.3% complication rate (major, 4.8%; minor, 10.7%), 2.6 days of average length of stay, and 5.5% unplanned readmission among elderly patients (>80) are significantly higher than younger patients. Although surgical indications and comorbidities are higher-quality predictors of complications, elderly patients should be appropriately counseled and medically optimized according to the perioperative risk profile before surgery.